Leadership Education as a Moving Target - Abell, Derek F. (Senate Hall Academic Publishing, 2005)
As the 21st century dawns it is already clear that leadership is not what it used to be. New challenges demand new capacities, and new approaches to leadership education. The new challenges have two distinct origins: transitions to broader responsibility further down the organization at earlier and earlier career points – in response to growing needs for entrepreneurial initiative and new growth; and fundamental changes in the landscape in which firms operate – in particular a growing need to join public and private sectors, technology and management, East and West, and today and tomorrow.This article is intended on the one hand to deepen our understanding of these changes and the new demands for professional, entrepreneurial, responsible, international, and culturally-grounded leaders, and on the other hand to lay out what the implications might be for leadership education itself. A key proposition is that “learning for leading” has very distinctive characteristics which require very distinctive educational approaches.
Keywords: entrepreneurial leadership; decentralization; responsible leadership; responsibility; career roadmaps; transitions; timeless leadership requirements; essentials; changing leadership; challenges; learning for leading; learning